2005
DOI: 10.1002/bdrc.20044
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutritional programming of fetal adipose tissue development: Long‐term consequences for later obesity

Abstract: As obesity reaches epidemic levels in the United States there is an urgent need to understand the developmental pathways leading to this condition. Obesity increases the risk of hypertension and diabetes, symptoms of which are being seen with increased incidence in children. Adipocyte development begins in the fetus and, in contrast to all other tissues whose growth ceases in late juvenile life, it has the capacity for "unlimited" growth. In normal healthy individuals, the increase in fat mass with age is acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 90 publications
(101 reference statements)
0
50
0
1
Order By: Relevance
“…LGA infants may be a consequence of maternal hyperglycaemia in late pregnancy which is not detected by the routine screening test for gestational diabetes mellitus (157) . A study of Japanese newborns found the morbidity rate of newborns excluding idiopathic hyperbilirubinaemia to be 10 %, which increased with gestational age and was accompanied by an increment of birth trauma.…”
Section: Large For Gestational Agementioning
confidence: 99%
“…LGA infants may be a consequence of maternal hyperglycaemia in late pregnancy which is not detected by the routine screening test for gestational diabetes mellitus (157) . A study of Japanese newborns found the morbidity rate of newborns excluding idiopathic hyperbilirubinaemia to be 10 %, which increased with gestational age and was accompanied by an increment of birth trauma.…”
Section: Large For Gestational Agementioning
confidence: 99%
“…1 Obesity in childhood and adolescence not only leads to increased incidence of hypertension, diabetes and morbidity, but also to adult obesity and its related adverse metabolic and cardiovascular sequelae. 2 Once obesity is established, it may be less amenable to population-based lifestyle interventions than predicted. 3 Adipocyte development begins in the fetus and has the capacity for 'unlimited' growth; 2 thus, exploring the determinants of body composition and understanding which early-life events regulate adipose tissue distribution in offspring are likely to provide important insights for novel interventions that may prevent excess adiposity in later life.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, there is a growing body of evidence from epidemiological studies in humans and from controlled investigations in animal models that genome regulation is largely modified by the nutritional environment such as an amount and composition of nutrients available to the offspring during prenatal and neonatal periods. [23][24][25][26][27] There are numerous studies showing that a suboptimal intrauterine environment, as well as suboptimal nutrition during early neonatal life alters development. 22 This situation can predispose the individual to lifelong health problems like metabolic syndrome or related diseases (such as glucose intolerance, insulin resistance, cardiovascular disease, hypertension, and obesity).…”
Section: Malnutritionmentioning
confidence: 99%